Biglycan, tumor endothelial cell secreting proteoglycan, as possible biomarker for lung cancer. Issue 9 (11th March 2021) - Morimoto, Hirofumi; Hida, Yasuhiro; Maishi, Nako; Nishihara, Hiroshi; Hatanaka, Yutaka; Li, Cong; Matsuno, Yoshihiro; Nakamura, Toru; Hirano, Satoshi; Hida, Kyoko
Abstract: Objectives: In lung cancer, surgery remains the most curative treatment and limited resection is beneficial for patients with low cardiopulmonary function and low malignancy tumors. However, there are no biomarkers of low malignancy to select candidates for limited resection without compromising the outcome of treatments. Recently we identified biglycan (BGN) as a tumor endothelial cell (TEC) marker that is associated with tumor progression in various cancers. In this study, we analyzed the association between BGN expression in TECs in lung cancer and cancer progression in patients. Materials and Methods: First, we performed immunohistochemistry of BGN with resected lung tumor tissues of 155 patients who had undergone thoracic surgery and analyzed the correlation between BGN‐positive vessel density in primary lung tumors and clinicopathological factors. Second, we measured the BGN levels in preoperative serum of other 46 patients with lung cancer by ELISA, and analyzed the correlation between BGN expression in tumor tissues and blood BGN levels. Results: High BGN expression in the TECs was significantly associated with T factor, and was a significant negative predictor. BGN levels in preoperative serum of 46 patients with lung cancer was significantly correlated with BGN expression in the TECs. Preoperative serum BGN level was significantly lower in healthy volunteers and less invasive adenocarcinoma than in invasive adenocarcinoma and other lung carcinomas. These results suggest that low BGN level in preoperative serum in patients with lung cancer might indicate low malignancy. Conclusions: BGN can be a potential biomarker for lung cancer. Abstract : We found that biglycan (BGN) is expressed in tumor endothelial cells (TECs) and that BGN expression in TECs is associated with tumor progression and prognosis in lung cancer. Moreover, BGN expression in preoperative serum was significantly associated with BGN expression in TECs and with tumor malignancy.